The lesion characteristics assessed by LGE‐MRI after the cryoballoon ablation and conventional radiofrequency ablation. Issue 2 (13th January 2018) - Kurose, Jun; Kiuchi, Kunihiko; Fukuzawa, Koji; Mori, Shumpei; Ichibori, Hirotoshi; Konishi, Hiroki; Taniguchi, Yayoi; Hyogo, Kiyohiro; Imada, Hiroshi; Suehiro, Hideya; Nagamatsu, Yu‐ichi; Akita, Tomomi; et al.
Abstract: Background: Rhythm outcomes after the pulmonary vein isolation (PVI) using the cryoballoon (CB) are reported to be excellent. However, the lesions after CB ablation have not been well discussed. We sought to characterize and compare the lesion formation after CB ablation with that after radiofrequency (RF) ablation. Methods: A total of 42 consecutive patients who underwent PVI were enrolled (29 in the CB group and 13 in the RF group). The PVI lesions were assessed by late gadolinium enhancement magnetic resonance imaging 1–3 months after the PVI. The region around the PVs was divided into eight segments: roof, anterior‐superior, anterior‐carina, anterior‐inferior, bottom, posterior‐inferior, posterior‐carina, and posterior‐superior segment. The lesion width and lesion gap in each segment were compared between the two groups. Lesion gaps were defined as no‐enhancement sites of >4 mm. Results: As compared to the RF group, the overall lesion width was significantly wider and lesion gaps significantly fewer at the anterior‐superior segment of the left PV (LAS) and anterior‐inferior segment of the right PV (RAI) in the CB group (lesion width: 8.2 ± 2.2 mm vs 5.6 ± 2.0 mm, P  = .001; lesion gap at LAS: 7% vs 38%, P  = .02; lesion gap at RAI: 7% vs 46%, P  = .006). Conclusions: The PVI lesions after CB ablation were characterized by extremely wider and more continuous lesions than those after RF ablation.